PENGARUH UKURAN PERUSAHAAN, VARIABILITAS PENDAPATAN DAN OPERATING LEVERAGE PADA STRUKTUR MODAL INDUSTRI PERBANKAN - Arie Abimanyu, Made Kharisma; Pradnyantha Wirasedana, Wayan (E-Jurnal Akuntansi; Vol 11 No 3 (2015), 2015)
Capital structure is a phenomenon specific to the banking industry because unlike other industries. Substitution auditor is a behavior that is done by the company to switch auditors. The purpose of research is to mengetahai effect of firm size, operating leverage, earnings variability in the capital structure of the banking industry listed on the Stock Exchange in the period 2011 to 2013. The sampling method using purposive sampling, the sample size of 30 companies bank. Data analysis techniques are multiple linear regression analysis and classical assumption. The results of this study are company size, operating leverage and earnings variability effect on the capital structure of the banking industry which is listed on the Stock Exchange the period of 2011 through 2013
Keywords: Company size, variability Revenue, Operating Leverage, Capital Structure